Stress Levels and Associated Factors Among Nursing Students From Different Ethnic Groups in Malaysia - K. Mangaikresh, Krishnan; Chew, Ming Tsuey *; Bradley, D.A. *; Soon, Lean Keng (Faculty of Medicine and Health Sciences, 2022)
Introduction: Nursing education and training is known to be an inherently stressful experience and poses challenging demands for students. The aim of this study is to evaluate the stress levels among nursing students from different ethnic groups in Malaysia. Methods: This cross-sectional study recruited the January to February 2020 nursing students from a private university in Malaysia with a self-administered questionnaire. Participants’ level of stress was measured using the Perceived Stress Scale (PSS) developed by Sheu and colleague in 2002. Data collected were analyzed with, One-way ANOVA and Spearman analysis to determine the significant factors associated with stress. Results: Two hundred nursing students across years one to three enrolled. The mean monthly household (family) income was MYR4686.25 ± 4660.38. Stress was significantly associated with ethnicity and monthly household (family) income (p< 0.05). Bonferroni post-hoc test demonstrated that the mean stress level of Malay students is statistically significant compared to Chinese and Indian students (p< 0.001). The PSS determined the nursing students’ stress level to be moderate. Conclusion: The association of stress levels with ethnicity, and monthly household (family) income suggested the need for suitable cultural and sufficient financial support for nursing students to reduce their stress levels.